1997
DOI: 10.1212/wnl.48.2.453
|View full text |Cite
|
Sign up to set email alerts
|

Two large Spanish pedigrees with nonsyndromic sensorineural deafness and the mtDNA mutation at nt 1555 in the 12S rRNA gene

Abstract: We describe two unrelated Spanish families with isolated sensorineural hearing loss. In both pedigrees, the deafness was transmitted maternally, which suggested a mitochondrial, DNA (mtDNA) defect. Within the same pedigree, some relatives showed aminoglycoside-induced deafness, whereas others were not exposed to aminoglycosides before the onset of hearing loss. Molecular genetic analysis in both families showed the A-to-G transition at nt 1555 (A1555G) in the mitochondrial 12S rRNA gene. In one pedigree, the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 4 publications
1
41
0
Order By: Relevance
“…We found 1555A > G at a frequency of 2.6% in the cohort, and the fact that only case reports have previously been published on this mutation likewise suggests that it is rare among patients with SNHI. 4,8,9 In contrast, every patient with matrilineal hearing impairment in a Spanish cohort was found to harbour 1555A > G. 10 The discrepancy in the observed frequencies may be explained by several factors. Firstly, ascertainment bias may be involved, 16 as our results are based on patients detected in population-based registers, while the patients reported by Estivill et al 10 were selected from several clinical centres or were obtained through advertisements in the public media.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We found 1555A > G at a frequency of 2.6% in the cohort, and the fact that only case reports have previously been published on this mutation likewise suggests that it is rare among patients with SNHI. 4,8,9 In contrast, every patient with matrilineal hearing impairment in a Spanish cohort was found to harbour 1555A > G. 10 The discrepancy in the observed frequencies may be explained by several factors. Firstly, ascertainment bias may be involved, 16 as our results are based on patients detected in population-based registers, while the patients reported by Estivill et al 10 were selected from several clinical centres or were obtained through advertisements in the public media.…”
Section: Discussionmentioning
confidence: 92%
“…The mutation 1555A > G was the first to be identified, 4 and interestingly, it also appears to confer an increased risk of hearing impairment in conjunction with the use of aminoglycosides. 4 The mutations 7445A > A and 7472insC have been reported only in selected families [5][6][7] and 1555A > G in small series of cases 4,8,9 except for a recent study, where a very high frequency of 1555A > G has been observed among Spanish families with maternally inherited sensorineural hearing impairment. 10 In order to study the prevalence of these mtDNA mutations among patients with SNHI we identified cases by reviewing registers at the audiological units serving a specific population and collected cases that fulfilled certain criteria including family history data.…”
Section: Introductionmentioning
confidence: 99%
“…The first mutation, an A to G substitution at position 1555 in the 12S rRNA gene (1555A®G), was reported in a large Israeli-Arab family with maternally inherited, non-syndromic hearing loss. 3 This mutation was also found in many other pedigrees with non-syndromic deafness, [4][5][6] and in patients and families with aminoglycoside-induced ototoxic hearing impairment. 4,[7][8][9] Apparently this mutation makes individuals susceptible to hearing impairment after treatment with aminoglycosides at concentrations that normally do not affect hearing.…”
Section: Introductionmentioning
confidence: 66%
“…The 2 families examined in this study were of Spanish origin and were partially described in another study [el Schahawi et al, 1997]. All individuals studied were interviewed at the Neurology Service of the Hospital Donostia.…”
Section: Methodsmentioning
confidence: 99%
“…The most plasmy. These studies have proposed that the level of heteroplasmy could influence the clinical manifestations of the disease [del Castillo et al, 2003;el Schahawi et al, 1997].…”
Section: Introductionmentioning
confidence: 99%